2020
DOI: 10.3390/d12040130
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Predation Drives Assembly of Adriatic Fish Communities

Abstract: We performed over 19,000 lure-assisted, underwater visual fish census transects at over 140 shallow coastal sampling locations in the mid- eastern Adriatic sea of the Croatian mainland and islands, recording all fish taxa observed, their predatory behavior in response to the lure, and the cover of benthic habitats with which they were associated. We hypothesized that prey habitat preference was a learned or selected response to aggressive behavior by piscivorous mesopredators, and predicted that mobile prey wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Research carried out on fish communities from vegetated and unvegetated habitats in eastern Adriatic Sea showed that prey and predators resulted negatively associated in various habitats and this negative correlation was as much stronger as predators were more aggressive. In this geographic area prey showed a positive association with C. nodosa and P. oceanica, besides unconsolidated sediments, in agreement with our analysis (Kruschel and Schultz 2020).…”
Section: Patterns Of Functional Diversitysupporting
confidence: 92%
See 2 more Smart Citations
“…Research carried out on fish communities from vegetated and unvegetated habitats in eastern Adriatic Sea showed that prey and predators resulted negatively associated in various habitats and this negative correlation was as much stronger as predators were more aggressive. In this geographic area prey showed a positive association with C. nodosa and P. oceanica, besides unconsolidated sediments, in agreement with our analysis (Kruschel and Schultz 2020).…”
Section: Patterns Of Functional Diversitysupporting
confidence: 92%
“…Our results are drawn from a high number of heterogeneous studies applying different sampling methods in different seasons, taking into consideration only seagrass habitats without bare substrates, and skipping details on predation mode. As stated in dedicated studies, local environment may play a main role in producing different patterns of prey/predator association through habitat patchiness, interspecific interactions, fishing activities and many other variables (Kruschel and Schultz 2020). Nevertheless, the signal of segregation between aggressive predators that are associated with P. oceanica and C. nodosa and their putative prey, that tend to occupy other seagrass habitats, seems to be strong enough to be recorded by our broad analyses at the whole basin scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexistence with C. gigas (Staglicic et al 2020). Listed as present in Novigrad and Karin Seas, but no further mention (Kruschel et al 2011). Cyprus no no O. edulis present in species list (Fischer 1997).…”
Section: Croatia No Nomentioning
confidence: 99%
“…This is a clear example of the complex interplay between predator ecological constraints and prey adaptation in response to varying selective pressures. Kruschel and Schultz [61] censused Adriatic fish communities and found that aggressive predators appear to drive prey species to habitats where less aggressive predators are found, changing both the types of predators that they encounter and the ecological context in which they encounter these predators. This work shows how some predators indirectly affect the evolution of prey traits through other selective agents.…”
Section: Why a Special Issue On This Topic?mentioning
confidence: 99%